Marketing Management : Analysis, Planning, Implementation, and Control - Kotler, Philip, author 301835 (Upper Saddle River, NJ : Prentice Hall, 1997)
An analysis of trends and developments in global marketing management. The book includes a section on brand development as one of the keys to successful marketing. Emphasis is placed on managing business processes and core competencies, not just departmental functions. Also emphasized is the importance of teamwork between marketing and all the other functions of the business. Different perspectives are introduced in strategic market planning. The text provides company examples of creative, market-focused action.